F1 hybrid rice growth differences in growing conditions - ., Gusmiatun; ., Minwal; Amir, Nurbaiti (International Journal of Engineering and Technology, 2019)
One effort to increase national rice production is to utilize dry land, this is because many wetlands changed into the non-agricultural sector. On the other hand, the productivity of rice in dry land is generally lower than paddy rice, because farmers typically use local varieties because it feels suit the tastes of the local community. For that, there need to be new varieties that have high production and flavor to taste the communities where these varieties will be developed. This is to increase the interest of farmers grows rice on dry land. Assembly of new varieties has been conducted in Phase-1 and the resulting F1 hybrid plants (JTLDR-G-416). This study aims to determine the yield potential of the F1 hybrid plants in different soil conditions, namely rice paddies, and fields. Placement varieties in the field using a randomized block design and repeated 4 times. The varieties used are F1 hybrids, varieties (Parental Jati Luhur and Dayang Rindu), as well as high-yielding varieties (Inpago-7 and Ciherang). The parameters studied were plant height, number of tillers per hill, number of panicles per hill, number of grains per panicle, filled grains per cent, grain weight of 1000 grains and grain weight per clump. The results showed that the production of the F1 hybrid is better than the varieties Lady Longing and Jati Luhur. If F1 hybrids planted in the fields, then a higher production Â± 7.1% compared with the dry land.Â Â